2004
DOI: 10.1097/00006982-200412000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Functional Characteristics in Adult Vitelliform Macular Dystrophy

Abstract: Purpose: Detailed morphologic and functional evaluation of adult vitelliform macular dystrophy (AVMD).Methods: The records of 61 consecutive AVMD patients (inclusion criterion: vitelliform lesion smaller than one disk diameter at least in one eye) were evaluated retrospectively regarding visual acuity, color vision, perimetry, retinal pigment epithelium (RPE) autofluorescence, fluorescein angiography, electro-oculography, full-field and multifocal electroretinography, and molecular genetic evaluation of the VM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(66 citation statements)
references
References 38 publications
2
56
0
8
Order By: Relevance
“…32 In various degenerative retinal disorders, increased FAF correlated with lipofuscin accumulation, whereas reduced or absent FAF indicated blockage (eg, retinal vessels), loss of RPE cells, or absence of RPE phagocytosis. 26,27,[33][34][35][36][37][38][39][40] The patterns of FAF distribution in RP patients observed in this study are similar to those reported previously. Ophthalmoscopically preserved areas of RPE at the posterior pole correspond to detectable FAF.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…32 In various degenerative retinal disorders, increased FAF correlated with lipofuscin accumulation, whereas reduced or absent FAF indicated blockage (eg, retinal vessels), loss of RPE cells, or absence of RPE phagocytosis. 26,27,[33][34][35][36][37][38][39][40] The patterns of FAF distribution in RP patients observed in this study are similar to those reported previously. Ophthalmoscopically preserved areas of RPE at the posterior pole correspond to detectable FAF.…”
Section: Discussionsupporting
confidence: 86%
“…The diagnosis was established in each patient by one author (UK) based on patient and family history, ophthalmoscopy, visual field testing, and full-field or multifocal electroretinography according to the standards of the International Society for Clinical Electrophysiology of Vision. [25][26][27][28][29] The range of normal FAF and NIA images was evaluated in one eye of 25 healthy subjects aged 12-70 years without ocular disease. These subjects had normal visual acuity for the eye examined and no abnormalities on ophthalmoscopy.…”
Section: Methodsmentioning
confidence: 99%
“…Clinically, BVMD 15 and AFVD 16 present with vitelliform lesion at the macula that progress through stages over time but usually the central vision is preserved until late in the disease. In comparison with BVMD, AFVD 16 is a milder disease with a later onset and slower progression. In contrast, ARB presents early in life with central visual acuity loss, irregular RPE alterations, and whitish sub-retinal deposits, 14,17 and is associated with higher incidence of angle closure glaucoma.…”
Section: Discussionmentioning
confidence: 98%
“…259 However, the generalized reduction in mfERG responses was only seen in 14% of eyes in the study by Renner et al and these findings may suggest a large variability in the extent of retinal dysfunction in AVMD. 247 Scholl et al also demonstrated that mfERG amplitude significantly correlated with visual acuity and the stage of disease. 271 Because mfERG abnormalities are often detected in Best disease and AVMD patients with good visual acuity, mfERG may serve as an indicator of the extent of retinal functional impairment in these patients.…”
Section: Best Disease and Adult Onset Vitelliform Macular Dystrophymentioning
confidence: 93%
“…51,224,246,247,250,259,271 Most studies have demonstrated that the majority of patients with Best disease and AVMD have reduced P1 amplitude in the central 5--10 of the retina with sparing of peripheral response amplitudes. 71,224,246,247,250,271 The mfERG implicit times are generally not affected in most patients. Saito et al reported generalized reductions in response amplitudes throughout the macula in 92% of patients with AVMD, suggesting the impairment in retinal function is not only limited to the central macula.…”
Section: Best Disease and Adult Onset Vitelliform Macular Dystrophymentioning
confidence: 99%